Students’ perceptions of Integrated Performance Assessments: Towards an effective assessment model focused on communicative ability (Letras, 2019)
In the field of foreign and second language teaching, current trends in curriculum development highlight the importance of creating performance-based assessment instruments focused on the three modes of communication: interpretive (aural or reading comprehension without the possibility of negotiating meaning with the creator of the message), presentational (written or oral communication without the possibility of negotiating meaning with the reader/interlocutor) and interpersonal (oral or written two-way communication with the possibility of negotiating meaning with the reader/interlocutor) (The National Standards Collaborative Board 2015). As previous studies (Adair-Hauck, Glisan et al. 2006, Davin, Troyan et al. 2011, Adair-Hauck & Troyan 2013, Zapata 2016, Levi Altstaedter & Krosl 2018; among others) have shown, Integrated Performance Assessments, are a viable option for this kind of assessment approach. A crucial aspect of the teaching-learning process are students’ perceptions, as these can impact their performance on tasks and assessments. Although previous studies have focused on students’ perceptions of IPAs, (Zapata 2016, Levi Altstaedter & Krosl 2018), more research is needed on this topic. Therefore, this study investigates the relationship among variables such as perceptions of effectiveness of IPAs, assessment anxiety, perceptions of instrument design, and students’ satisfaction, while offering a theoretical model that presents a connection among those variables and offers a theoretical model that includes the conections among those variables.
Keywords: assessment - communicative ability – anxiety - perceptions